Provenancing Nineteenth Century Saltpetre From British India Using Nitrogen, Oxygen, and Strontium Isotope Ratios. Issue 2 (June 2022) - Mizota, Chitoshi; Hansen, Robin; Hosono, Takahiro; Okumura, Azusa; Shinjo, Ryuichi; Aizawa, Masataka
Highly purified specimen of saltpetre, kept in two glass jars are stored in the collections of the Natural History Museum, London, United Kingdom. Historic catalogs of the specimen collection record their acquisition date as 17th March, 1881. The specimen represent heritage of the saltpetre industry during the times of the colonial British India. Chemical analysis shows that they are highly refined, containing only traces of impurities. Dual isotopic composition (δ 15 N and δ 18 O) of nitrate implies their intrinsic origin as British India. In addition, relative to highly radiogenic signature of Sr widespread throughout India, less radiogenic strontium ( 87 Sr/ 86 Sr = 0.707859–0.714168) in the specimens suggests that final stages of the refining took place in western India where relevant waters containing pristine Sr were used. Stable isotope geochemistry in combination with history and socio-economy provide new insights into this research area which is not yet fully understood.